High prevalence of simultaneous rib and vertebral fractures in patients with hip fracture. Issue 2 (February 2017) - Lee, Bong-Gun; Sung, Yoon-Kyoung; Kim, Dam; Choi, Yun Young; Kim, Hunchul; Kim, Yeesuk
Abstract: Purpose: The purpose was to evaluate the prevalence and location of simultaneous fracture using bone scans in patients with hip fracture and to determine the risk factors associated with simultaneous fracture. Patients and methods: One hundred eighty two patients with hip fracture were reviewed for this study. Clinical parameters and bone mineral density (BMD) of the lumbar vertebra and femoral neck were investigated. To identify acute simultaneous fracture, a bone scan was performed at 15.4 ± 4.1 days after hip fracture. The prevalence and location of simultaneous fracture were evaluated, and multivariate logistic regression analysis was performed to determine the risk factors. Results: Simultaneous fracture was observed in 102 of 182 patients, a prevalence of 56.0%. Rib fracture was the most common type of simultaneous fracture followed by rib with vertebral fracture. The BMD of the lumbar vertebra was significantly lower in patients with simultaneous fracture (p = 0.044) and was identified as an independent risk factor (odds ratio: OR 0.05, 95% confidence interval: CI 0.01–0.57). Conclusions: The prevalence of simultaneous fracture was relatively high among patients with hip fracture, and BMD was significantly lower in patients with simultaneous fracture than in patients without it. Surgeons should be aware of the possibility of simultaneous fracture in patients with hip fracture.